Full-driving soft robotic colonoscope in compliant colon tissue. (17th November 2017) - Wang, Kundong; Ma, Jiayi; Wang, Feng; Wang, Zhiwu; Yan, Guozheng; Zhou, Yilu
Abstract: Robotic colonoscopy is an efficient examination method for finding malignant tumour in its early stage. This research developed a novel robotic endoscope with 13 mm diameter, 105 mm length and 22.3 g weight. A contact biomechanical model is proposed to increase the locomotion safety and efficiency in the soft tissue. The model shows that the friction difference between the robot and the tissue is a key factor to locomotion capability. A soft, full bellow with excellent compatibility was designed to package the robot body. The bellow increased the static friction and decreased the kinetic friction given the change in the contact state. The bellow is divided into three segments. Each segment is composed of a linear locomotor with micromotor, turbine-worm and wire wrapping–sliding mechanism. The robot is tested in in vivo pig colon, which revealed an excellent locomotion capability and safety in soft tissues.